(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
Currently, the existing regulatory documents in the republic are aimed at protecting the environment, preserving public health, taking into account developing industries. The development of preventive measures is of great importance. Since in order to prevent and prevent the environmental consequences of modern industrialization, a comprehensive assessment of the state of the natural environment and environmental use of resources are necessary.